DISTRIBUTION OF SPAWNING AND NURSERY GROUNDS FOR DEEP–WATER RED SHRIMPS IN THE CENTRAL WESTERN MEDITERRANEAN SEA - PALMAS, F.; ADDIS, P.; CABIDDU, S.; CUCCU, D.; FOLLESA, M. C.; MURA, M.; OLITA, A.; PESCI, P.; SABATINI, A. (Mediterranean Marine Science, 2014)
The presence of spawning and nursery grounds of Aristeids in the central western Mediterranean Sea were investigated using fishery-independent data (trawl surveys, 1994–2012). Spatial distributions were generated for mature animals and recruits, for both spring/summer and autumn data, using an inverse distance weighted deterministic interpolation. The persistence index was used to identify stable spawning and nursery grounds in the Sardinian slope region for Aristaeomorpha foliacea and Aristeus antennatus. Areas of aggregation for recruits and mature females appear connected with important physical habitat features. The analysis also suggests a seasonal bathymetric distribution for nursery areas. The recruits of A. foliacea are located in the upper part of the continental slope (377-450 m) in spring-summer and reach greater depths (468-628 m) in autumn. For A. antennatus, for which nursery areas only emerge in autumn, there is presumably an opposite ontogenic migration, from deep sea to upper slope, during the summer (575-681 m). Results indicate also a partial overlap between the nursery and spawning grounds of both species. In this particular areas, local environmental conditions such as upwelling events or the presence of canyons and seamounts seem to play an important role in their distribution. This study generated also relevant information on the spatial and temporal distribution of seasonal or persistent aggregations of spawners and recruits, providing scientific elements to suggest the feasibility of protecting these important resources.